Presence of Human Papillomavirus (HPV) Apolipoprotein B Messenger RNA Editing, Catalytic Polypeptide-Like 3 (APOBEC)–Related Minority Variants in HPV-16 Genomes From Anal and Cervical Samples but Not in HPV-52 and HPV-58. (17th May 2018) - Mariaggi, Alice-Andrée; Péré, Hélène; Perrier, Marine; Visseaux, Benoit; Collin, Gilles; Veyer, David; Le Hingrat, Quentin; Ferré, Valentine Marie; Joly, Véronique; Couvelard, Anne; Bucau, Margot; Davitian, Carine; et al.
Abstract: Background: The aim of this study was to investigate the presence of minority variants (MVs) in high-risk human papillomavirus (HPV) types (HPV-16, -52, and -58) from cervical and anal smears. Methods: Whole HPV genome ultra-deep sequencing (UDS) was performed on cervical and anal smears collected during patient follow-up. Bioinformatics analyses were performed using Bowtie2 (Geneious). Results: We assessed 55 HPV-16–positive, 20 HPV-52–positive, and 17 HPV-58–positive samples, with significant differences in patient characteristics for the 2 anatomic sites. HPV-16 MVs were detected in 20 samples (36%), with no difference between cervical and anal samples. We did not find an association between the presence of MVs and cytovirological parameters. Seven HPV-16 genomes (13%) were apolipoprotein B messenger RNA editing, catalytic polypeptide-like 3 (APOBEC) edited. Among the cervical HPV-16–positive samples, most MVs (55%) resulted from APOBEC-related mutations. MVs were detected in 10 HPV-52–positive (50%) and 12 HPV-58–positive (71%) samples, with no difference between cervical and anal samples. No APOBEC-related mutations were found on HPV-58 or HPV-52 genomes. Conclusions: Overall, high-risk HPV MVs were found in about half of all cases in both anal and cervical samples. Interestingly, we reported for the first time a differential impact of APOBEC3 mutagenic activity depending on high-risk HPV type. Abstract : Ultra-deep sequencing of whole genomes of 3 high-risk human papillomavirus types (HPV-16, -52, -58) from cervical and anal smears showed minority HPV variants in 46% of samples, mainly generated by APOBEC mutagenic activity in the case of cervical HPV-16 samples.